2011
DOI: 10.1159/000332915
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Hepatic 11β-Hydroxysteroid Dehydrogenase-1 Expression in Calcium-Deficient Rats

Abstract: Background: Many epidemiologic studies have reported a link between calcium (Ca) deficiency and metabolic syndrome. In this study, we examine Ca deficiency in rats and whether changes in glucocorticoid metabolism are induced. Methods: Twelve-week-old female Wistar rats were weaned onto a very-low-Ca diet (low-Ca group) or a control diet (control group) for 2 weeks. Quantitative real-time PCR was used to assess mRNA for 11β-hydroxysteroid dehydrogenase-1 (11β-HSD1), 11β-HSD2, phosphoenolpyruvate carboxykinase, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 54 publications
0
7
1
Order By: Relevance
“…We previously reported that Hsd11b1 expression in the liver increases in response to a Ca-deficient diet in adult rats for 2 wk [23]. In our current study, however, the expression of Hsd11b1 mRNA in male offspring (DD) from Ca-deficient dams was lower than that in male offspring (CC) from control dams.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…We previously reported that Hsd11b1 expression in the liver increases in response to a Ca-deficient diet in adult rats for 2 wk [23]. In our current study, however, the expression of Hsd11b1 mRNA in male offspring (DD) from Ca-deficient dams was lower than that in male offspring (CC) from control dams.…”
Section: Discussioncontrasting
confidence: 78%
“…We previously reported that a low Ca diet alters glucocorticoid metabolism, leading to hepatic up-regulation of Hsd11b1 in rats [23]. We also reported that feeding a Ca-restricted diet to pregnant rats results in hypomethylation and decreased expression from the Hsd11b1 promoter in the liver of offspring at day 21 [24].…”
Section: Introductionmentioning
confidence: 85%
“…Genomic methylation is considered an epigenetic mechanism important for developmental programming, an area that is currently of high interest to nutrionists and other basic scientists. Many dietary and nutritional interventions have a significant impact on biological functions and disease susceptibilities via alterations to epigenetic programming [10][11][12]22,31]. Nutrition, among many other environmental factors, is a key player that can induce epigenetic changes not only in the directly exposed organisms but also in subsequent generations because of transgenerational inheritance of epigenetic modifications.…”
Section: Discussionmentioning
confidence: 99%
“…Calcium deficiency in the early post-weaning stage is associated with a reduction in adiponectin release from isolated rat mesenteric adipocytes [21]. We recently reported that a low-Ca diet alters glucocorticoid metabolism, which in turn leads to up-regulation of Hsd11b1 in rat liver tissues [22].…”
Section: Introductionmentioning
confidence: 99%
“…Calcium (Ca) plays an important role in the pathogenesis of insulin resistance and obesity, suggesting that hypocalcemia is a risk factor for developing these conditions [1,2,3]. Several reports have shown an inverse relationship between Ca intake and body fat mass [2,4,5,6].…”
Section: Introductionmentioning
confidence: 99%